Risk factors for falls among community-dwelling older adults: A systematic review and meta-analysis - Li, Ying; Hou, Lingyu; Zhao, Hanping; Xie, Rongrong; Yi, Yue; Ding, Xiaorong (Frontiers in Medicine, 2023)
Background and Objective: Falls among elderly living in the community are frequently fatal. A retrospective analysis was used in this study to identify risk factors for falls in community-dwelling older adults. This research aimed to collect published studies to find risk factors for falls in community-dwelling older adults. Methods: We searched for literature from the founding of PubMed, EMBASE, the Cochrane Library, the China Biomedical Literature Database (CBM), the China National Knowledge Infrastructure (CNKI), and the China Science and Technology Periodicals Database (VIP), and the Wanfang Database until January 25, 2022.The studies were selected using inclusion and exclusion criteria. We collected information from relevant studies to compare the impact of potential risk factors such as age, gender, and mental illness on falls among community-dwelling older adults. Results: A total of 15 studies were included, with 12,016 community seniors. Fear of falling (OR=1.64), age (OR=1.11), female gender (OR=1.28), balance disorder (OR=1.72), and depression (OR=1.34) were significant risk factors that contributed to falls in the elderly in the community. Conclusion: This study provides preliminary evidence that falls among community-dwelling older adults are associated with factors such as age, gender, balance disorders, and depression. The results of this research may help improve clinician awareness, risk stratification, and fall prevention among community-dwelling older adults.